2016
DOI: 10.1097/mlr.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bias by Emergency Department Providers in Care for American Indian Children

Abstract: Background American Indian children have high rates of emergency department (ED) use and face potential discrimination in health care settings. Objective Our goal was to assess both implicit and explicit racial bias and examine their relationship with clinical care. Research Design We performed a cross-sectional survey of care providers at five hospitals in the Upper Midwest. Questions included American Indian stereotypes (explicit attitudes), clinical vignettes and the Implicit Association Test (IAT). Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 60 publications
0
74
0
Order By: Relevance
“…The Black‐White Race IAT was used in the eight studies examining a preference for white people compared to black people . The researchers in one study developed their own IAT to examine implicit bias toward American Indians versus white people, although it is important to note that the IAT used in this study was not validated. In addition to the Black‐White IAT, several studies incorporated other versions of the IAT, including the social class IAT, medical compliance IAT, and quality care IAT.…”
Section: Resultsmentioning
confidence: 99%
“…The Black‐White Race IAT was used in the eight studies examining a preference for white people compared to black people . The researchers in one study developed their own IAT to examine implicit bias toward American Indians versus white people, although it is important to note that the IAT used in this study was not validated. In addition to the Black‐White IAT, several studies incorporated other versions of the IAT, including the social class IAT, medical compliance IAT, and quality care IAT.…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated that a majority of ED care providers in 5 EDs (84%) had implicit preference for non-Hispanic white children or adults compared with those who were American Indian. 18 Another recent study found that resident physicians had implicit racial bias against African American children that was similar to levels of bias against African American adults. 19 This emerging body of work indicates that being a child does not protect against the experience of implicit bias.…”
mentioning
confidence: 98%
“…8 In another study of five EDs in the upper Midwest, physicians, nurses, and advanced practice providers were found to have implicit preference for non-Hispanic white patients, as measured by both the IAT and using clinical vignettes. 9 Moreover, American Indian children were viewed as more challenging than other children. Approaches to imaging in children can also be affected by implicit bias.…”
Section: Data On Implicit Biasmentioning
confidence: 99%